An Application of the Information Entropy to Nuclei - Massen, S. E. (HNPS Advances in Nuclear Physics, 2021)
Shannon’s information entropies in position- and momentum-space and their sum S are calculated for various s-p and s-d shell nuclei using a correlated one-body density matrix depending on the harmonic oscillator size b_0 and the short range correlation parameter y which originates from a Jastrow correlation function. It is found that the information entropy sum for a nucleus depends only on the correlation parameter y through the simple relation S= s_0A + s_1A y^-λ_sA , where s_0A, s_1A and λ_sA depend on the mass number A. Finally, we propose a method to determine the correlation parameter from the above property of S as well as the linear dependence of S on the logarithm of the number of nucleons.